Modern contraceptive use among female refugee adolescents in northern Uganda: prevalence and associated factors - Ritah Bakesiima; Amanda Cleeve; Elin Larsson; James K. Tumwine; Grace Ndeezi; Kristina Gemzell Danielsson; Rose Chalo Nabirye; Jolly Beyeza Kashesya (BMC, 2020)
Abstract Background Adolescent pregnancies are persistently high among refugees. The pregnancies have been attributed to low contraceptive use in this population. The aim of this study was to determine the prevalence and factors associated with modern contraceptive use among female refugee adolescents in northern Uganda. Methods This was a cross sectional study using both descriptive and analytical techniques. The study was carried out in Palabek refugee settlement in Northern Uganda from May to July 2019. A total of 839 refugee adolescents who were sexually active or in-union were consecutively enrolled. Interviewer administered questionnaires were used for data collection. Results Modern contraceptive prevalence was 8.7% (95% CI: 7.0 to 10.8). The injectable was the most commonly used modern contraceptive method [42.5% (95% CI: 31.5 to 54.3)], and most of the participants had used the contraceptives for 6 months or less (59.7%). Reasons for not using modern contraceptives included fear of side effects (39.3%), partner prohibition (16.4%), and the desire to become pregnant (7.0%). Participants who were married (OR = 0.11, 95% CI: 0.04 to 0.35, p < 0.001), cohabiting (OR = 0.43, 95% CI: 0.20 to 0.93, p = 0.032) or having an older partner (OR = 0.93, 95% CI: 0.86 to 0.99, p = 0.046) were less likely to use modern contraceptives. Conclusion Modern contraceptive use among female refugee adolescents was very low, and few reported a desire to become pregnant, leaving them vulnerable to unplanned pregnancies. Least likely to use modern contraceptives were participants who were married/cohabiting and those having older partners implying a gender power imbalance in fertility decision making. There is an urgent need for innovations to address the gender and power imbalances within relationships, which could shape fertility decision-making and increase modern contraceptive use among refugee adolescents.